Pengaruh Kompensasi Terhadap Kepuasan Kerja Karyawan - Liani, Endah Nur; Pramanik, Nuniek Dewi (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
This study aims to determine the effect of compensation on employee job satisfaction at the Ir. H. Djuanda Training Center of PT. Kereta Api Indonesia. This research employs a quantitative method with purposive sampling, resulting in a total sample of 40 respondents. Data collection was conducted using a Likert-scale questionnaire distributed to employees at the Ir. H. Djuanda Training Center. The data analysis techniques used include validity tests and t-tests. The data obtained from the questionnaires were processed by the author using SPSS 25. Based on the results of the t-test, the calculated r-value was 6.948, which is greater than the table r-value of 2.037, and a significant value of 0.001 < 0.05 was obtained, indicating that the dependent variable has an effect on the independent variable. Furthermore, the coefficient of determination test resulted in an R Square of 55.9%. Referring to the analysis, it can be concluded that compensation has an impact on employee job satisfaction.